If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3 + 5x = 4x + 6 Reorder the terms: -3 + 5x = 6 + 4x Solving -3 + 5x = 6 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -3 + 5x + -4x = 6 + 4x + -4x Combine like terms: 5x + -4x = 1x -3 + 1x = 6 + 4x + -4x Combine like terms: 4x + -4x = 0 -3 + 1x = 6 + 0 -3 + 1x = 6 Add '3' to each side of the equation. -3 + 3 + 1x = 6 + 3 Combine like terms: -3 + 3 = 0 0 + 1x = 6 + 3 1x = 6 + 3 Combine like terms: 6 + 3 = 9 1x = 9 Divide each side by '1'. x = 9 Simplifying x = 9
| 4+6x=5x+8 | | 3x+10=19+2x | | 6x+6=-24-4x | | -6x-10=3x+44 | | -x+3=-15-7x | | (4x-5)*(2x-5)=105 | | h(x)=9x/(6x-11) | | 7a+2=26+3a | | 2ab+5ba+3ab= | | cx^2-(a^2+b^2)x+ab=o | | 2-4ln(x)=7 | | 2.2=6.1+y | | 0.65x+0.05(12-x)=0.10(-90) | | .065x+0.05(12-x)=0.10(-90) | | 88x^4/121x | | 6-3(4x-6)=-6 | | ln(x/y)-ln(10) | | ln(x/10*y) | | 2+7a=65 | | 5x-4=5(x-9) | | -4(x+8)=-44 | | p=a+3+c | | 5(w-4)=25 | | 4.1y=20.5 | | 10y-5=5y+5 | | 5b-6=8b | | 9x-9=40 | | -6x-14x=40 | | 5c-8c=21 | | 7a+2=26+39 | | 8x+9=2+6x+4 | | x-3y+3=0 |